The Impact of Nursing Care Management Implementation on the Improvement of a Centralized Nursing Information System - Siokal, Brajakson; Wahyuningsih, Wahyuningsih; Yani, Ahmad (Poltekkes Kemenkes Palu, 2024)
Nursing care management improves the centralized nursing information system by ensuring accurate documentation, efficient workflows, and better technology training, as well as supporting clinical decision-making with quality data. This study aims to assess the impact of nursing care management implementation on the improvement of the centralized nursing information system at IS Makassar Hospital in 2023. A quasi-experimental design with pretest and posttest was used, involving a control group, with a sample size of 110 nurses from 4 inpatient wards participating in the study through total sampling. Data were analyzed using the Wilcoxon test and independent paired t-test. The results showed a significant impact of nursing care management implementation on the centralized nursing information system. The intervention group had a p-value of 0.002, and the difference between the intervention and control groups showed a p-value of 0.0002. These findings indicate that structured nursing care management improves nurses' documentation skills and knowledge. It is recommended to explore the optimization of continuous training for nurses in the use of the centralized nursing information system, and to conduct a long-term evaluation of the impact of nursing care management implementation on the quality of documentation.